Personality and resilience in medical students (Studia Doctoralia Psychology and Educational Science, 2019)
This study has three main objectives: to establish the relationships between personality traits and resilience in medical students, the relationships between vulnerability factors and the level of resilience in medical students, and the relationships between personality traits, resilience and symptoms of depression, anxiety, stress among medical students. In this study participated 134 students enrolled at the University of Medicine and Pharmacy in Craiova, both in the specialization of general medicine and general medicine nurses, aged between 18 and 25 years, M = 19.78, SD = 1.31. Of these, 34 are men and 100 are women. The instrument used were Inventory of vulnerability / protection factors (α = .79), Resilience Scale, short form, RS-14 (α = .87),  five sets of 10 items each in five sub-domains of NEO PI-R: neuroticism, extraversion, openness to experiences, aggreableness, and conscientiousness (α > .70), and  Depression, Anxiety, and Stress Scales, DASS 21-R (α > .70). Resilience was negatively corelated with neuroticism, positively correlated with extraversion, and also positively correlated with conscientiousness. The protective factors were positively associated with resilience. Neuroticism has an increasing effect on depression, while extraversion has a decreasing effect on depression, neuroticism has an increasing effect on anxiety and stress, and aggreableness has a decreasing effect on stress. The results also showed that a high level of resilience leads to a low level of depression, anxiety, and stress.
Keywords: medical students; resilience; personality; depression; anxiety; stress